Front Cover: Design and Fabrication of Temperature‐Sensitive Nanogels with Controlled Drug Release Properties for Enhanced Photothermal Sterilization (Chem. Eur. J. 72/2017). Issue 72 (26th September 2017) - Li, Luoyuan; Fu, Limin; Ai, Xicheng; Zhang, Jianping; Zhou, Jing
Abstract : Designed PEDOT@PNIPAAm nanogels were fabricated by using temperature‐sensitive hydrogel [poly( N ‐isopropylacrylamide) (PNIPAAm)] to encapsulate poly(3, 4‐ethylenedioxythiophene) (PEDOT) nanoparticles (photothermal agents) and curcumin through a reformative precipitation polymerization. When triggered by near‐infrared light (NIR), the nanogels exhibited high photothermal conversion efficiency, and excellent temperature‐sensitive effects. The light induced temperature increase can weaken the interaction between the networks of PNIPAAm and curcumin to exert antioxidant and antibacterial performances. More information can be found in the Full Paper by L. Fu, J. Zhou et al. onpage 18180 .